Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/bip.23273
|View full text |Cite
|
Sign up to set email alerts
|

NCα‐gem‐dimethylated peptoid side chains: A novel approach for structural control and peptide sequence mimetics

Abstract: The design of linear peptoid oligomers adopting well‐defined secondary structures while mimicking defined peptide primary sequences is a major challenge in the context of drug discovery. To this end, chemists have developed cis‐inducing peptoid side chains to build robust polyproline type I helices. However, the number of efficient examples remains scarce and chemical diversity accessible through the use of these side chains is limited. Herein, we introduce an array of NCα‐gem‐dimethylated peptoid residues mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…[34] On the other hand, sterically controlled peptoids, show little variations in K cis/trans values with change in solvent, which can be seen for tert-butyl and NC α -gem-dimethylated side chains containing peptoids 26, 33-35. [45][46][47] Although theoretical models have been proposed for folding of natural peptides, reports on designing of such model to study the solvation effect on peptoid folding are limited. [62] In a view to unravel the forces that stabilise the peptoid foldamers in the presence of a solvent, Broda and co-workers theoretically (MP2 based method) delineated the effect of a polar environment on a peptoid models 79 and 80 (Figure 16).…”
Section: Effects Of Solvent On the Cis-trans Isomerization Of Peptoid...mentioning
confidence: 99%
See 1 more Smart Citation
“…[34] On the other hand, sterically controlled peptoids, show little variations in K cis/trans values with change in solvent, which can be seen for tert-butyl and NC α -gem-dimethylated side chains containing peptoids 26, 33-35. [45][46][47] Although theoretical models have been proposed for folding of natural peptides, reports on designing of such model to study the solvation effect on peptoid folding are limited. [62] In a view to unravel the forces that stabilise the peptoid foldamers in the presence of a solvent, Broda and co-workers theoretically (MP2 based method) delineated the effect of a polar environment on a peptoid models 79 and 80 (Figure 16).…”
Section: Effects Of Solvent On the Cis-trans Isomerization Of Peptoid...mentioning
confidence: 99%
“…Recently, Shyam et al incorporated NC α -gem-dimethylated amines in peptoids. [47] Introduction of such gem-dimethylated functionalities is expected to increase the diversity of peptoid Figure 6. A) Chemical structure and crystal structure of 25.…”
Section: Achiral α-Branched Aliphatic Side Chainsmentioning
confidence: 99%
“…Based on previous work, the N ‐ tert ‐butyl peptoid amides of the synthesized oligomers have a cis ‐conformation [15–16] . In previous study, NMR and computational studies have also shown that despite the absence of chirality, Nt Bu peptoid oligomers adopt preferentially the PPI‐like helical conformation thanks to a network of weak interactions such as intramolecular CO( i )⋅⋅⋅HC( i ‐n) hydrogen bonds and t Bu⋅⋅⋅ t Bu London interactions [24] .…”
Section: Resultsmentioning
confidence: 80%
“…Sterically hindered side‐chains could also favor the cis conformation of the N , N ‐disubstituted amide as observed with the naphtylethyl side‐chain [13] or with sterically hindered aliphatic groups [7,12,14] . Among the latter, the tert ‐butyl ( t Bu) [15] and NC α‐ gem ‐dimethylated [16] side‐chains totally lock the amide in the cis conformation whatever the solvent used (Figure 1c). Despite the potential of the tert ‐butyl group as cis ‐amide inducer, [17] oligomers containing this side‐chain are still rare in the literature and such peptoids exhibiting biological activities have never been reported.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation